Influence of organizational learning and innovation on organizational performance in Asian manufacturing food industry - Hui, Huang; Wan Mohamed Radzi, Che Wan Jasimah; Jenatabadi, Hashem Salarzadeh; Abu Kasim, Farihah; Radu, Son (Asian Economic and Social Society, 2013)
The main objective of this paper is to find out the impact of organizational learning (OL) and organizational innovation (OI) on organizational performance (OP) in Asia manufacturing food industries. This study explores those linkages using structural equation modelling (SEM) with data from 172 companies in food manufacturing companies was selected from Taiwan, China, and Malaysia. The research model includes three latent variables including OL, OI, and OP. The results showed that OL and OI have positive effect on OP.